Characterization And Process Recovery Of Refractory Gold Ores From Central Belt Malaysia - Sopheak, In (2019)
Gold mineralization in Central Belt, Malaysia, occurred along with a low grade metasedimentary volcanic terrain. The relationship between silicate and sulfide in this area is complicated. Therefore, gold characterization and pre-concentration processes (gravity concentration and froth flotation) are very important since it can reduce the amount of gangue minerals and the chemical consumption in further processes. Studies on S-Stockpile, S-G8 and S-G9 samples show that they contain mainly quartz and sulfide minerals such as stibnite, pyrite, arsenopyrite, and galena. Gold was found in both as “visible gold” and “invisible gold”. Free milling gold was mostly identified in S-Stockpile sample from fine to coarse grain (about 100µm). In S-G8 and S-G9 samples gold particles were observed as fine free milling form, interlocking and also as inclusion or as solid solution in sulfide minerals, mainly stibnite, pyrite, arsenopyrite, and galena. Panning of S-Stockpile sample with two different sizes (-1.25mm) and (-100µm) do not help in upgrading the gold due to fine and flaky in shape of gold particles were floated out of the pan. However, the pre-concentration by froth flotation of S-G8 and S-G9 samples by using 100, 200, and 300g/t of Aerofloat 208 or Aerophine 3418A promoters were able to recover the gold interlocking in sulfide minerals at pH 4, 6, and 8. Certain percentage of free milling gold particle was also floated to the concentrate due to the entrainment. Comparatively, Aerophine 3418A promoter had stronger in gold and sulfide recovery than Aerofloat 208 promoter, especially at pH 6 with a dosage of 200g/t.